Entre as interfaces das racionalidades da saúde: por que terapia floral? - Castro, Graciele Dotto (2011)
Western science, today, is science that has been instituted and comes in the first place, with characteristics such as objectivity, measurement and Cartesianism. This study brings to light, in a way, an old debate about what science is. And, behind that backdrop, reveals itself the central question: what reasons have led some doctors, immersed in the biomedical rationality and, consequently, in the Western scientific rationality, to look at other rationalities of health, getting to choose to work with at least one of them, the floral medicine, main theme of this study. Just this, a medicine based on other rationality of health, on other scientific rationality and, therefore, another understanding of individual, disease, health, treatment and cure. While the Western medical science focuses its gaze on diseases, organs and injuries and it is still slow, floral medicine - which is one of the complementary medicines is starting to look at the individuals and their relation with themselves and their surroundings to think about healing and illness, it looks at the person in all his relations to make his diagnosis and treatment, without fragmenting the individual and his body. Through content analysis of Bardin (2010), held with eight interviews with doctors who also work with floral medicine in the city of Porto Alegre, six categories were observed, which indicate the differences of the rationalities and the influences of each one in their work and also the reasons for the choice of floral medicine as a tool in the treatment of sick individuals, or better, of individuals with some physical, mental or emotional imbalance. The categories are: 1. What is illness? 2. What is healing? 3. What is health? 4. How does Western science work; 5. How does floral medicine work; 6. The path from biomedicine to floral medicine. These categories indicate the way of thinking of doctors during their life history and their professional history, what has influenced them and even led them up to work with floral therapy. Some of them already had in their lives factors and concepts that were the pillars to whet their curiosity about other forms of care with patients that complemented what they learned with medicine. Other doctors, fully immersed in the Western medical and scientific rationality, were caught by surprise by the effects of floral in their lives or in the lives of people nearby, which made them rethink their actions as doctors. All, however, when in contact with floral medicine, claimed to have noticed in this the possibility of helping their patients and themselves in the art of curing human suffering, thereby obtaining results that were and are interesting or even amazing. Maybe this surprise is not only because of the results, but because of the approximation that the study of floral made possible between these doctors and their patients, and thus between these doctors and the art of healing, making them even more curing agents of individuals and not just of illness or injuries.